Acute toxicity and tissue distribution of CdSe/CdS‐MPA quantum dots after repeated intraperitoneal injection to mice. Issue 9 (25th June 2012) - Haque, Md. Mamunul; Im, Hye‐Yeon; Seo, Ji‐Eun; Hasan, Mahbub; Woo, Kyoungja; Kwon, Oh‐Seung
ABSTRACT: Quantum dots (QDs) are novel tools with multiple biological and medical applications because of their superior photoemission and photostability characteristics. However, leaching of toxic metals from QDs is of great concern. Therefore, for the successful application of QDs in bioscience, it is essential to understand their biological fate and toxicity. We investigated toxicological effects and tissue distribution of mercaptopropionic acid‐conjugated cadmium selenide/cadmium sulfide (CdSe/CdS‐MPA) QDs after repeated intraperitoneal injection into BALB/c mice. The mice were injected every 3 days with various doses of QDs (0, 5, 10 and 25 mg kg −1 ). The subsequent effects of QDs on plasma levels of various biomarkers were evaluated at different time points (at 0, 1, 4, 7, 10, 13 and 15 days). Various tissue samples (spleen, liver, lung, kidneys, brain, heart and thymus) were collected for toxicity analysis, distribution testing, histopathological examination and inflammation assessment. No abnormal clinical signs or behaviors were recorded but the body weight of mice treated with 25 mg kg −1 QDs was significantly decreased from day 7 compared with control mice. QDs were observed in the liver, spleen, lung and kidneys, but not in brain or heart. Significantly higher levels of lactate dehydrogenase and nicotinamide adenine dinucleotide phosphate oxidase were found in the plasma, liver and spleen. Histopathological examination did not show any tissue toxicity but the levels of interleukin‐6, a pro‐inflammatory marker, were increased in the plasma, liver and spleen. All of these findings provide insight into the observed toxicological effect levels and tissue‐specific distribution of CdSe/CdS‐MPA QDs. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : BALB/c mice were injected every 3 days with various doses of CdSe/CdS‐MPA QDs. Body weight of the mice treated with 25 mg/kg QDs was significantly decreased from day 7. The QDs were observed in the liver, spleen, lung, and kidneys, but not in brain, or heart. Significantly higher levels of LDH and NADPH oxidase were found in plasma, liver, and spleen. Histopathological examination did not show any tissue toxicity but IL‐6 levels were increased in the plasma, liver, and spleen.